2022
DOI: 10.33087/ekonomis.v6i2.591
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Likuiditas, Profitabilitas, Leverage, dan Aktivitas dalam Memprediksi Financial Distress pada Perusahaan Subsektor Retail Trade yang Terdaftar di BEI

Abstract: The purpose of this study is to analyze how financial ratios can affect the prediction of financial distress or financial distress in retail trade sub-sector companies listed on the Indonesia Stock Exchange. In this study, liquidity is represented by the Current Ratio, profitability is proxied by the rate of return on assets (ROA). Leverage is represented by the Debt to Equity Ratio, and the activity ratio is represented by total asset turnover (TATO). The dependent variable used is financial distress with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
1
Order By: Relevance
“…Meanwhile, research conducted by Arifin et al (2021) and Dwiantari (2021) states that profitability proxied by ROA has a significant negative effect on financial distress. This is in contrast to research conducted by Susanti & Takarini (2022) which states that profitability has no significant effect on financial distress.…”
Section: Introductioncontrasting
confidence: 99%
“…Meanwhile, research conducted by Arifin et al (2021) and Dwiantari (2021) states that profitability proxied by ROA has a significant negative effect on financial distress. This is in contrast to research conducted by Susanti & Takarini (2022) which states that profitability has no significant effect on financial distress.…”
Section: Introductioncontrasting
confidence: 99%
“…The company needs a sufficient amount of cash from current assets to fulfill its current obligations. The results of this study are in line with previous research conducted by (Susanti and Takarini., 2022), Arohmawati and Pertiwi (2021), and (Ariqoh and Yuniningsih., 2022), which state that liquidity has a positive effect on financial distress. However, this research is different from research conducted by Rachmawati & Nur (2021), Kushidayati & Nur (2021) and Susilo & Suwaidi (2022), which state that liquidity does not contribute to financial distress.…”
Section: Effect Of Liquidity On Financial Distresssupporting
confidence: 93%
“…The high level of debt increases the possibility of default, which can have Financial Distress Analysis with Firm Size as a Moderating Variable in the Restaurant, Hotel, and Tourism Sub-Sector Companies on the Stock Exchange of Indonesia a devastating effect on the company's finances. Research carried out by Susanti and Takarini (2022) and Putri and Aminah (2022), have demonstrated that leverage has a favorable and significant impact on predicting financial distress. H3: Leverage is positively impacted to financial distress.…”
Section: Effect Of Leverage On Financial Distressmentioning
confidence: 99%